2022
DOI: 10.1002/anie.202204035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Negatively Curved Nanocarbon Molecule with an Octagonal Omphalos via Design‐of‐Experiments Optimizations Supplemented by Machine Learning

Abstract: A saddle‐shaped nanocarbon molecule was synthesized, which revealed the existence of negative Gauss curvatures on a >3‐nm molecular structure possessing 192 π‐electrons. The synthesis was facilitated by a protocol developed with Design‐of‐Experiments optimizations and machine‐learning predictions, and spectroscopy and crystallography were used to reveal the saddle‐shaped structure of the molecule. Solution‐phase analyses showed the presence of dimeric assembly, and crystallographic analyses revealed the stacke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…The ΔG difference between these complexes was largely ascribed to the entropy (– T Δ S ). Similarly, favourable entropy contributions for the association (– T Δ S < 0) were observed with complexes with large curved π-systems in preceding studies of nanocarbon molecules 22 , 28 31 , which was most likely due to desolvation of solvent molecules from the curved surface. Therefore, we believe that the large favourable entropy gain with [4]CQ (– T Δ S ~ 4 kcal mol –1 ) should be best explained by changes in the solvation in the presence of N,O-heteroatoms.…”
Section: Resultsmentioning
confidence: 68%
“…The ΔG difference between these complexes was largely ascribed to the entropy (– T Δ S ). Similarly, favourable entropy contributions for the association (– T Δ S < 0) were observed with complexes with large curved π-systems in preceding studies of nanocarbon molecules 22 , 28 31 , which was most likely due to desolvation of solvent molecules from the curved surface. Therefore, we believe that the large favourable entropy gain with [4]CQ (– T Δ S ~ 4 kcal mol –1 ) should be best explained by changes in the solvation in the presence of N,O-heteroatoms.…”
Section: Resultsmentioning
confidence: 68%
“…In our previous investigation of the “DoE+ML” strategy, [6] we developed an efficient method for the synthesis of 8Me‐[8]CMP ( 2 ) via a dimerization reaction of quaterphenyl 1 a (Figure 3). The 3×3×3 parameter space comprising ( M , T , C ), where M is equivalent of Ni(cod) 2 , T is the addition time of 1 a , and C is the final concentration of 1 a , was designed, and runs specified by the L 9 (3 4 ) table‘s coordinates were performed to fill 27 datasets for the yields of dimeric product ( 2 ) (see also Figure 2 of ref.…”
Section: Resultsmentioning
confidence: 99%
“…However, applications of DoE and empirical models to synthetic organic chemistry have not yet been fully exploited, and further investigations are awaited, which should incorporate data‐driven science in organic synthesis [4,5] . We recently demonstrated that DoE optimization combined with machine‐learning (ML) supplements can afford an empirical performance model for a macrocyclization reaction [6] . In short, a 3‐factor parameter space was designed with 3‐tier (3‐level) parameters, and 9 experimental runs were allocated by adopting Taguchi's orthogonal array of “L 9 (3 4 )” to effectively fill the 3×3×3 space in an evenly scattered manner (Figure 1a) [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic compounds, which in the early days of organic chemistry were considered to have a tendency to be planar, can actually adopt various nonplanar molecular shapes. 3,4 The development of contemporary synthetic methods in combination with researchers' imagination and creativity has enabled the preparation of elusive, threedimensional structures including circulenes, 5-9 cycloparaphenylenes (CPPs), [10][11][12][13] carbon nanobelts (CNBs), [14][15][16][17][18] large phenine frameworks 19,20 and impressive, all-benzene interlocked catenanes and trefoil knot. 21 Moreover, embedding non-hexagonal rings in a graphenic lattice causes warping of the -system, due to geometric mismatch of adjacent rings.…”
Section: Introductionmentioning
confidence: 99%